Coping After Disaster: Socially Embedded Coping Among Landslide-Affected Communities in Indonesia - Firli Sunaryoko; Eleonora Martins; Gesang Satriatama; Dina Ruslanjari; Sri Rum Giyarsih; Retnadi Jatmiko (Journal of Educational, Health and Community Psychology, 2026)
This study explored psychological coping strategies among communities affected by the landslide in Banaran Village, Ponorogo Regency, Indonesia. It aimed to identify the coping strategies adopted by survivors and examine the contextual factors shaping their use. A qualitative descriptive design with thematic analysis was employed. Primary data were collected through semi-structured interviews with six affected residents selected based on variations in gender, age, and level of disaster exposure. Two key informants from local disaster-related institutions were also interviewed to support contextual understanding and data triangulation. Data were analyzed using Braun and Clarke’s thematic analysis approach. The findings show that survivors employed both emotion-focused and problem-focused coping strategies that evolved according to personal experiences and post-disaster conditions. Emotion-focused coping was reflected in religious acceptance, emotional sharing, and support from family and peers, whereas problem-focused coping involved livelihood restoration, preparedness efforts, and heightened environmental vigilance. Gendered and age-related tendencies also emerged, although these were not rigid categories. Female participants more often emphasized relational and emotionally supportive coping, while male participants more often framed coping through responsibility, future-oriented thinking, and practical adaptation. Older participants tended to prioritize household continuity and long-term stability, whereas younger participants relied more on companionship, external encouragement, and moral-religious reflection. Overall, coping practices were socially and culturally embedded within religious values, family relationships, and collective recovery experiences. Psychosocial recovery did not necessarily involve the disappearance of fear, but rather the capacity to continue everyday life alongside persistent environmental uncertainty.